Kebutuhan Personel Air Traffic Controller (ATC) Di Bandara Sultan Mahmud Badaruddin II Palembang - Susetyadi, Ari; Nurhayati, Yati (Warta Penelitian Perhubungan, 2012)
Assessment of personnel needs of air traffic controllers (ATC) at the Sultan Mahmud Airport Badaruddin II Palembang is to find out how many number of needs of air traffic controllers (ATC) at the Sultan Mahmud Airport Badaruddin II Palembang that has with standards / regulations by the !CAO to support flight operations in order to ensure flight safety. Assessment method was quantitative method with the decomposition of descriptive, exposure and explanation in detail based on the compilation of primary data and secondary data that have been processed. The results of the assessment show that air traffic controller (ATC) at the Sultan Mahmud Airport Badaruddin II Palembang is still not adequate, there is still lack of abaout 11 air traffic controller (ATC) personnel at the Sultan Mahmud Badaruddin II Palembang Airport.Keywords : air traffic controller (ATC), Sultan Mahmud Badaruddin II Palembang Airport Pengkajian tentang kebutuhan personel air traffic controller (ATC) di Bandara Sultan Mahmud Badaruddin II Palembang adalah untuk mengetahui bagaimana jumlah kebutuhan air traffic controller (ATC) di Bandara sultan Mahmud Badaruddin II Palembang apakah telah memenuhi standar/peraturan yang ditetapkan oleh ICAO untuk mendukung kegiatan operasi penerbangan dalam rangka menjamin keselamatan penerbangan. Metode pengkajian yang digunakan adalah metode kuantitatif dengan penguraian ( deskriptif), pemaparan dan penjelasan secara rind berdasarkan kompilasi data primer dan data sekunder yang telah diolah. Hasil pengkajian menunjukan personel air traffic controller (ATC) di Bandara sultan Mahmud Badaruddin II Palembang masih belum memadai, yakni masih terdapat kekurangan sekitar 11 personel air traffic controller (A TC) di Bandara sultan Mahmud Badaruddin II Palembang. Kata Kunci: air traffic controller (ATC),Bandara Sultan Mahmud Badaruddin II Palembang